Involvement of the parabrachial nucleus in emergence from general anesthesia - Jia Li; Qiuyu Zhu; Jiaxin Xiang; Yiyong Wei; Donghang Zhang (Frontiers in Neuroscience)
The parabrachial nucleus (PBN), located in the dorsolateral pons, is involved in many important biological functions, such as sensory signaling, feeding, defensive behaviors, fear, anxiety, and sleep–wake cycles. General anesthesia shares the classical feature of reversible loss of consciousness with natural sleep, and accumulating evidence has indicated that general anesthesia and sleep–wake behaviors share some common underlying neural mechanism. In recent years, emerging studies have investigated the involvement of PBN in emergence from general anesthesia, but divergence exists in terms of different types of general anesthetics or different durations of treatment with the same group of general anesthetics. Here, we reviewed the current literature and summarized the evidence about the contribution of PBN to general anesthesia.